2016
DOI: 10.5009/gnl15229
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Bone Marrow-Derived Mesenchymal Stem Cells in Dextran Sulfate Sodium-Induced Murine Chronic Colitis

Abstract: Background/Aims: Bone marrow-derived mesenchymal stem cells (BM-MSCs) have shown beneficial effects in experimental colitis models, but the underlying mechanisms are not fully understood. We investigated the long-term effects of BM-MSCs, particularly in mice with chronic colitis. Methods: Chronic colitis was induced by administering 3% dextran sulfate sodium (DSS) in a series of three cycles. BMMSCs were injected intravenously into DSS-treated mice three times during the first cycle. On day 33, the therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…Accordingly, these results corroborated previous studies that showed the short-term protective efficacy of MSC on macroscopic and histopathological severity of inflammatory diseases, which has been correlated with the down-regulation of Th1 inflammation [23][24][25][26][27][28]33,37] and the suppression of collagen-reactive T cell-driven production of matrix degrading enzymes [38]. In agreement with the macroscopic findings, we observed that the colon from treated sick animals presented a higher frequency of re-epithelized areas that were repaired earlier.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, these results corroborated previous studies that showed the short-term protective efficacy of MSC on macroscopic and histopathological severity of inflammatory diseases, which has been correlated with the down-regulation of Th1 inflammation [23][24][25][26][27][28]33,37] and the suppression of collagen-reactive T cell-driven production of matrix degrading enzymes [38]. In agreement with the macroscopic findings, we observed that the colon from treated sick animals presented a higher frequency of re-epithelized areas that were repaired earlier.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, several clinical trials have shown short-term positive results in more than 200 nonresponsive patients with refractory IBD, in which MSC promoted a complete clinical remission in approximately 40% and an overall response in approximately 60% (for review, see Grégoire et al [19]). A few studies have showed that MSC injections persistently improved murine colitis by down-regulating Th1 inflammation [25], suppressing T cells [26], inducing T reg differentiation [27] and up-regulating T reg responses [28]. Nevertheless, despite these well-described short-term properties, little is known about long-term MSC effects on IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dooley and Ten Dijke [20] described the fibrogenic influence of TGF-β1 through the initiation of inflammation. CTGF is a crucial profibrogenic cytokine produced by activated HSCs, and TGF-β increases the buildup of ECM in the liver [17]. Paradis et al [21] reported CTGF over-expression in rat and human hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is in partial agreement with the findings of Zhao et al [4] who demonstrated that intravenous injection of BM-MSCs reduced IL-1β and IL-6 expression more than their intraperitoneal or intrahepatic injection. The immunosuppressive effect BM-MSCs is driven by the suppression of T lymphocyte proliferation, B cell function, and dendritic cell maturation [17].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that reducing neuro-inflammation could reduce both chronic ethanol intake ( maintenance ) and possibly relapse-like drinking. Developments in the stem cell field have shown that most tissues contain mesenchymal stem cells (MSCs; Prockop et al, 2010), known to be activated by inflammatory mediators (e.g., TNFα) in damaged areas, leading to the generation of anti-inflammatory cytokines including IL-10 (Lee et al, 2016) and a soluble TNFα receptor, which neutralizes TNFα (Yagi et al, 2010). MSCs can be isolated and expanded from a number of tissues, such as bone marrow and adipose tissue (Contador et al, 2015; Ezquer et al, 2016).…”
Section: Relapse-like Alcohol Intakementioning
confidence: 99%